Accelerated Aging Effect on Epoxy-polysiloxane Polymeric Insulator Material with Rice Husk Ash Filler - Tumiran .; Arif Jaya; Hamzah Berahim; Rochmadi . (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
The performances of outdoor polymeric insulators are influenced by environmental conditions. This paper presents the effect of artificial tropical climate on the hydrophobicity, equivalent salt deposit density (ESDD), surface leakage current, flashover voltage, and surface degradation on epoxy-polysiloxane polymeric insulator materials with rice husk ash (RHA). Test samples are made at room temperature vulcanized (RTV) of various composition of epoxy-polysiloxane with rice husk ash as filler. The aging was carried out in test chamber at temperature from 50oC to 62oC, relative humidity of 60% to 80%, and ultraviolet (UV)  radiation 21.28 w/cm2 in daylight conditions for 96 hours. The experiment results showed that the flashover voltage fluctuates from 34.13 kV up to 40.92 kV and tends to decrease on each variation of material composition. The surface leakage current fluctuates and tends to increase. Test samples with higher filler content result greater hydrophobicity, smaller equivalent salt deposit density, and smaller critical leakage current, which caused the increase of the flashover voltage. Insulator material (RTVEP3)showed the best performance in tropical climate environment. Artificial tropical aging for short duration gives less effect to the surface degradation of epoxy-polysiloxane insulator material. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.846